The Effect Of Liquidity And Intellectual Capital On Company Value Mediated By Profitability (Study of Advertising Printing Media Sub-sector Companies Registered on the IDX.) - Ariyanto, Eko; Rahayu, Yayuk Ngesti; Rokhman, M. Taufiq Noor (JURNAL MANAJEMEN MOTIVASI, 2025)
This study investigates the impact of liquidity and intellectual capital on company value, with profitability serving as a mediating variable, in the context of the Advertising, Printing, and Media sub-sector of the creative industry listed on the Indonesia Stock Exchange (IDX) from 2020 to 2023. Drawing on Signaling Theory and the Resource-Based View (RBV), this research explores how internal financial and intangible assets influence investor perceptions and company valuation. Using secondary data and a purposive sampling method, 19 companies were analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM). Liquidity was measured by the Current Ratio (CR), intellectual capital by Value Added Human Capital (VAHU), profitability by Return on Equity (ROE), and company value by Price to Book Value (PBV). The results reveal that liquidity significantly and positively affects company value, while intellectual capital exhibits a weak and insignificant impact. Profitability, surprisingly, shows a negative and significant effect on company value, and fails to mediate the relationship between liquidity and intellectual capital with company value. These findings highlight the centrality of liquidity in investor valuation decisions within this sub-sector, while also indicating a need for better strategic communication and optimization of intellectual capital to enhance company value. The study contributes to the literature by challenging the assumption of profitability as a consistent mediator and underscores the limited market appreciation for intangible assets in the creative industry. Future research is encouraged to explore additional mediators and conduct cross-sectoral analyses to enrich the understanding of value creation mechanisms in dynamic industries.